Automatic risk control based on FSA methodology adaptation for safety assessment in intelligent buildings - Mikulik, Jerzy; Zajdel, Mirosław (Zielona Góra: Uniwersytet Zielonogórski)
The main area which Formal Safety Assessment (FSA) methodology was created for is maritime safety. Its model presents quantitative risk estimation and takes detailed information about accident characteristics into account. Nowadays, it is broadly used in shipping navigation around the world. It has already been shown that FSA can be widely used for the assessment of pilotage safety.
Keywords: risk; formal safety assessment; fuzzy logic; intelligent building